An overview of China's regional trade agreements - Julia Lintunen (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
Since becoming a WTO member in 2001, China has negotiated numerous regional trade agreements with astonishing speed. This paper provides an overview of China's current free trade agreements and examines the economic importance of two major Asian regional trade agreements for China. The academic literature often treats China's free trade agreements as driven more by political, rather than economic, interests. The agreements are seen as shallow and concluded with minor economic partners. In fact, China's approach to trade agreements has evolved over time and cumulative impact of these agreements has been positive for trade between China and its agreement partners. The recently concluded Asian regional free trade agreement, the Regional Comprehensive Economic Partnership (RCEP), should positively influence trade for both China and other participating Asian countries. China could also benefit economically from joining the other major regional trade agreement, the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP).
urn:nbn:fi:bof-202101141038
Keywords: 330; trade policy; free trade agreements; RCEP; CPTPP